Using Technology as Learning Media to Enrich ESP Students' Speaking Skill for Indonesian Higher Education Students - Nurul Amaliah; Sunarlia Limbong; Nur Ina Syam; Fahmi Room; Khaliq Bashar (JPTK : JURNAL PENELITIAN TINDAKAN KELAS, 2023)
For everyone, learning a new language is a really difficult undertaking. It's considerably more difficult to receive an education in a foreign tongue. It takes a lot of time to learn how to read, understand, speak, and write flawlessly in a language. ESL students who attempt to navigate this challenging experience while living abroad encounters numerous language and communication issues. This qualitative case study research project's main goal was to identify the educational technology tools that participants used to advance their language and communication abilities. This study is based on the research question: "To what extent do Indonesian higher education students use technology on their own, outside of the framework of ESP class, to develop English language and communication skills?. The findings of this study imply that students use technology in their daily life for a variety of functions, particularly for their education. The use of educational technology tools is also considered as assisting teachers and students in becoming more successful, effective, and useful individuals in their daily lives. As conclusion that using technology as learning media can enrich ESP students' speaking skill for Indonesian higher education students.